Fruit Audio Aroma: Innovative Learning Media For Optimizing The Sense Of Touch, Listening, And Smell In Blind Children - Astuti, Egita Widya; Rohmatun, Isnaini Nur; Pratiwi, Ayu Resti Eka; Nugrahani, Dewi Wahyu; Lastomo, Danang Pamarsudi; Yulisetiani, Septi (Department of Special Education, 2022)
Education for blind children begins at the age of childhood and elementary school. At that age, blind children will begin to be introduced to fruits. However, in general, teachers in special schools will introduce fruits to blind children using only real fruit. This is considered ineffective, because the fruit recognition learning process only relied on the ability of the teacher that causes blind students to get bored quickly and the material presented by the teachers is not well received. Therefore we need a 3D fruit learning media designed according to the characteristics of blind children. The purpose of making Fruit Audio Aroma media is as a solution to overcome problems in the learning process of the blind children with disabilities related to fruit material. The method used is the observation method. The result of this study indicated that the Fruit Audio Aroma media provides maximum usability with easy and practical use, according to the needs of the blind through aroma, braille, texture, QR code and audio features that can be operated smoothly. Thus, this media is effective for increasing the sensitivity of the sense of touch, hearing and smell in blind children.